Pengaruh Kualitas Pelayanan, Disiplin Kerja, dan Fasilitas Terhadap Kepuasan Anggota Koperasi Simpan Pinjam Credit Union Sendang Jati Desa Penadaran - Sarmila Sarmila; Arif Wahyu Wirawan (Pusat Riset dan Inovasi Nasional, 2025)
Maintaining happy members is the first priority for every cooperative. The purpose of this research is to determine how the Sendang Jati Credit Union Savings and Loan Cooperative in Penadaran Village does in terms of member satisfaction with service quality, work discipline, and facilities. The research approach is quantitative in this study. In this study, we used a random sampling technique, which ensures that every element of the population has an equal chance of being chosen as a sample member. There are 91 respondents in the sample. It can be concluded that the service quality of the Sendang Jati credit union savings and loan cooperative in Penadaran village has a positive and significant influence on the satisfaction of its members, as the study found that the service quality variable had a t-value of 3.207> t table (1.988) and a significance value of 0.002 <0.05. Therefore, H2 is accepted. It can be concluded that work discipline has a positive and significant influence on the satisfaction of members of the Sendang Jati credit union savings and loan cooperative in Penadaran village, since the Work Discipline Variable has a t-value of 5.460> t table (1.988) and a significance value of 0.000 <0.05. Therefore, H3 is accepted. H4 is accepted, meaning that the Service Facilities variable has a positive and significant influence on the satisfaction of members of the Sendang Jati credit union savings and loan cooperative in Penadaran village, because the calculated t value of 4.743 > t table (1.988) and the significance value of 0.000 < 0.05.